2021
DOI: 10.3897/bdj.9.e66115
|View full text |Cite
|
Sign up to set email alerts
|

Ophiocordyceps aphrophoridarum sp. nov., a new entomopathogenic species from Guizhou, China

Abstract: Ophiocordyceps is the largest genus in the family Ophiocordicipitaceae, including many entomopathogenic species. In recent years, many species have been described in this genus, with a wide range of host insects. Entomopathogenic fungi include ecologically, economically and medicinally important species, but a large portion of their diversity remains to be discovered and described. In this study, a new species, Ophiocordyceps aphrophoridarum sp. nov, parasitising Aphrophoridae sp. (Hemiptera) is prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 558 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Previous studies have demonstrated that the use of these six genetic loci optimally resolves the phylogenetic placement of the species Pleurocordyceps (Xiao et al, 2018 , 2023 ; Wang et al, 2021 ; Wei et al, 2022 ). The nuclear gene amplification reactions followed the protocol outlined by Yang et al ( 2021 ). PCR products were sent to Tsingke Biotechnology for sequencing (Chongqing, China).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that the use of these six genetic loci optimally resolves the phylogenetic placement of the species Pleurocordyceps (Xiao et al, 2018 , 2023 ; Wang et al, 2021 ; Wei et al, 2022 ). The nuclear gene amplification reactions followed the protocol outlined by Yang et al ( 2021 ). PCR products were sent to Tsingke Biotechnology for sequencing (Chongqing, China).…”
Section: Methodsmentioning
confidence: 99%
“…About 2000 species of fungi are being described annually ( Cheek et al 2020 ). Entomopathogenic fungi have received great attention due to their ecological, economic and medical applications ( Yang et al 2021 ). However, the diversity of entomopathogenic fungi necessitates additional research.…”
Section: Introductionmentioning
confidence: 99%